A photoacoustics-enhanced drilling probe for radiation-free pedicle screw implantation in spinal surgery - Liu, Li; Zhao, Yongjian; Li, Ang; Yu, Xianghu; Xiao, Xiao; Liu, Siyu; Meng, Max Q.-H. (Frontiers in Bioengineering and Biotechnology, 2022)
This article proposes novel intra-operative navigation and sensing systems for pedicle screw insertion optimization to facilitate functionally accurate spinal fusion by combining the radiation-free and multi-scale sensing techniques, i.e., global context-awareness from the macroscopic 3D ultrasound (US) imaging, and local tissue-awareness from the in situ photoacoustic (PA) sensing at clinically relevant mesoscopic scale. More specifically, 3D US imaging was established for online state update of the spinal posture to determine the optimal entry point and coarse drilling path once non-negligible patient motion or relative motion between inter-vertebral segments occurs intra-operatively. Further, aiming to local navigation in a fine-grained manner, an advanced sensor-enhanced drilling probe was developed, which integrates a PA endoscopic imaging component for in situ tissue sensing. Such perceived PA signals from side-looking direction of the drill bit within the vertebrae could be employed to differentiate cancellous bone from harder cortical bone or weakened osteoporotic bone, whereby preventing cortical breach occurrence, strengthening implant stability as well as mitigating iatrogenic injuries of the neighbouring artery and nerves. To optimize the PA-augmented probe design, the light absorption spectrum of cortical bone and cancellous bone were in-virto measured and the associated PA signals were characterized. Eventually, a pilot validation study was performed on a ex vivo bovine spine using our proposed multi-scale navigation and sensing systems. The experimental results demonstrate the clinical feasibility, which holds great potential to enable functionally accurate screw implantation for spine stabilization with application in complex spine interventions.